Round window anatomy predicts ease of cochlear implantation in children. (October 2021) - Shim, Timothy; Zalzal, Habib; Kumar, Nankee; Tercyak, Samuel; Whitehead, Matthew T.; Reilly, Brian; Preciado, Diego
Abstract: Objectives: We aim to evaluate the utility of the Round Window Angle (RWA) as a predictor of difficulty and operative time in cochlear implantation. Methods: A retrospective study of pediatric patients that underwent cochlear implantation and CT temporal bone imaging from January 2008 to November 2019. Correlation, univariate, and multivariate analysis were conducted. Results: 347 implantations met inclusion criteria. We found a difference in RWA for difficult (median: 101°, n = 5) and non-difficult (median: 74, n = 317) implantations (p < 0.0001). There was also a difference in RWA in patients with round windows visualized intra-operatively (p < 0.0197). When controlling for age and intraoperative round window visualization, logistic regression showed RWA was significantly associated with difficult insertion (OR: 1.687; p = 0.0246). Further, there was positive correlation between RWA and operative time (r = 0.1779, p = 0.0013) with patients with acute RWAs having shorter operative times (mean 115 .7 ± 32.1 min) than those with obtuse RWA (mean 183.5 ± 97.0 min) (p = 0.0035). When accounting for surgeon and patient age, multivariate linear regression showed round window visualization (β = 3.456, p = 0.0006) and obtuse RWA (β = 6.172, p < 0.0001) was associated with an increase in operative time. Conclusion: Further research is needed to identify difficult cochlear implantations to increase the success and reduce risks associated with the surgery. Our study reports the possibility that an obtuse RWA both significantly increases difficulty and time of operation due to decreased round window visualization.